REASONS FOR PATIENT DELAYS & HEALTH SYSTEM DELAYS FOR TUBERCULOSIS IN SOUTH INDIA - Goel, Kapil; Kondagunta, Nagaraj; Soans, Shashi Joycee; Bairy, Althur Ramachandra; Goel, Parul (Indian Journal of Community Health, 2011)
Background: Globally, the burden of Tuberculosis is escalating. Early diagnosis and prompt initiation of tuberculosis treatment is essential for an effective tuberculosis control programme. Objectives: To study the self reported reasons for patient and health system (diagnosis & treatment) delays in Tuberculosis patients. Methods: A community based cross sectional study was conducted among 98 new sputum positive TB cases aged > 15 years registered under RNTCP from Oct 2006 to June 2007 & receiving treatment under DOTS in Udupi taluk by interviewing them. Results: Total 98 patients were recruited and 68% were males. Out of 17 patients with patient delays, 82% felt that their symptoms were not severe, 71% felt that patient delay was due to lack of awareness and 71% did not take it seriously. Out of 86 patients with health system delays, 82.6% of patients mentioned that doctor has not advised for sputum examination, 76.7% of patients told that they first consulted a private doctor, 21% of them mentioned that doctor was unaware to diagnose TB. Conclusion: Symptoms not severe is the main reason for the patient delay and doctor didn’t advise for sputum examination is the main reason for health system delays.